Use of Extra Virgin Olive Oil (EVOO) in the treatment of traumatic ulcers. A case report - Sinesi, Antonia; Casu, Cinzia; Cefola, Savino; Damato, Ruggiero; Orrù, Germano (Journal of Biomedical Practitioners, 2020)
Introduction Extra virgin olive oil (EVOO) is an essential food of the Mediterranean diet (MD) and some countries in the Mediterranean area such as Italy, Spain and Greece represent the largest and most important producers in the world. In Southern Italy, precisely all through the countryside of the north of Bari in Apulia, is produced a particular type of extra virgin olive oil by cultivar "Coratina" characterized by the presence of a high content of polyphenols, the highest compared to other cultivars (1) and very rich in biocompounds. Since the last century, it was customary for the inhabitants of the area to use it for the treatment of various diseases: burns, trauma, cheilitis and processes inflammation of various kinds. Over time, this practice has gradually disappeared and almost forgotten. In recent decades, numerous studies have been published which have documented most of the beneficial effects of the Mediterranean diet in promoting human health. Its beneficial effects can largely be attributed to the consumption of extra virgin olive oil (EVOO) (2). The consumption of extra virgin olive oil is able to reduce lipid and DNA oxidation, improve the lipid profile and insulin resistance, endothelial dysfunction, inflammation, reduce blood pressure in hypertensive patients and modify the response of the immune system (3, 4). Despite its extensive use and although numerous studies on extra virgin olive oil have shown its remarkable effectiveness in healing skin burns (5, 6, 7), bedsores (8) and foot wounds in the diabetic patient (9), no scientific studies have been proposed for the treatment of traumatic ulcers in the oral cavity. In this case - report, we decided to use EVOO as a therapeutic aid in the treatment of mucosal oral injury in a prosthesis on implant-bearer patient. Key words: extra virgin olive oil, polyphenols, “Coratina” cultivar, traumatic ulcers.